Impementasi Asy-Syu’ara dalam Good Village Governance Sebagai Upaya Pencegahan Kecurangan Pengelolaan Keuangan Desa - Brilian Nanda Arifian; Mohamad Djasuli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine the application of the content of Asy-Syu'aaraa in good village governance as an effort to prevent fraud in village financial management. The type of research used is qualitative research with a case study approach, namely by using primary data such as observation, interviews and documentation. The result of this research is that the content of Surah Ash-Syu'ara as a guideline is able to provide benefits to the community, especially the village government in village financial management by providing the values of trustworthiness, accountability and transparency, justice, and participation. The application of these values can increase public trust, reduce the risk of corruption, and ensure the effective and efficient use of village funds. By adopting these principles, village governments can realize good governance, improve community welfare, and create a more transparent and accountable government environment.